Endoscopic Management of Pharyngocutaneous Fistula: A Case Report - Mandar Vijay Doiphode; Pankaj Nemade; Mahesh Rangrao Mahadik; Arvinder Singh; Hamilton John Reyes Landayan (Journal of Digestive Endoscopy)
Pharyngocutaneous fistula is a comparatively rare complication following neck surgery, presenting challenges in management and potential morbidity. These patients are difficult to treat by any conventional techniques and often a multidisciplinary approach is required for treating such patients. Here, we present a case of a 43/M patient who developed a pharyngocutaneous fistula following anterior discectomy for cervical compression. Since endoscopy provides a minimal invasive approach for managing such complex cases, we decided to use endoscopic fistula plug insertion in this patient. This case underscores the importance of early recognition and tailored intervention in the management of pharyngocutaneous fistulae.